Criminal and penal policy in contemporary Polish reality (Archives of Criminology, 2012)
The article discusses criminal policy, understood as court procedures intended to counteract and limit crime by applying provisions of criminal law. The chapter begins with an analysis of diverse definitions of criminal and penal policy. Then, mechanism of action of such policies in the aspect of administering punishments to perpetrators of criminal deeds is discussed. An analysis of statistical data concerning administering particular types of punishments allows to draw certain conclusions concerning penal policy employed in Poland in the difficult period of social change. The most often administered punishment in the first decade of the 21st century is deprivation of liberty (imprisonment) with conditional suspension (probation), imprisonment and fines are slightly less frequent, the least frequently courts sentence unconditional imprisonment. The picture of the data allows only to make a draft of contemporary visions of solving social problems related with crime – or rather lack of such visions. The reasons of incoherence and – in many cases – irrationality of our criminal policy can be seen in many factors which are impossible to discuss or even list in one article. However it is worth to notice that undoubtedly the progressing expansion and politicization of criminal law should be limited and it should be acknowledged that criminal law is not the best remedy for social problems, which include crime.